Gigantic Liver Abscess in Pregnancy : A Rare Case - Yusrawati yusrawati; Reyhan Julio Azwan (Universitas Andalas, 2023)
Liver abscess (LA) is defined as a suppurated cavity caused by invasion and multiplication of microorganisms within liver parenchyma. Incidence of LA is rare with 20/100,000 admissions. Etiology of LA can be bacterial, parasitic, mixed or more rarely fungal. Amoebic liver abscess (ALA) is one of the most sequelae invasive amoebiasis with 44.1% LA in patients were caused by ALA.. Early treatment initiation is important to avoid the potential risks of preterm delivery, fetal infection, perinatal mortality, multi-organ dysfunction, sepsis, septic shock, and even maternal death. Methods tis research was case report :Â A 27 year old patient diagnosed with G1P0A0L0 16-17 weeks of pregnancy with LA, previously the patient went to Emergency room with complaint of upper right abdominal pain since a week and getting worsed since 1 day. The patient also complaint fever and swelling at the right abdomen. From physical examination found swelling and tenderness in the right abdomen, palpable flat surface mass and dim percussion. From an ultrasound examination is a single intrauterine live fetus, gravid 16-17 weeks according to biometry, a hypoechoic mass appeared measure 11.6 x 9.6 cm, suspected liver abscess. Then she underwent laparoscopy abscess drainage with digestive surgery collaboration, from hystopathology the result was chronic inflamation acute exaserbation might from liver abscess. Liver abscess (LA) during pregnancy is an extremely rare condition. Pregnancy has been described as a risk factor for LA because of immunological changes. Imaging modalities should be chosen with caution in the pregnant patient